IMPLEMENTATION BY TYPE OF COOPERATIVE LEARNING GROUP INVESTIGATION TO INCREASE ACTIVITY AND RESULTS OF LEARNING IPS - Suasta, I Gede (Jurnal Ilmiah Ilmu Sosial, 2016)
This research was conducted in SMP Bhaktiyasa Singaraja in the Academic Year 2009/2010 with the purpose of improving the activity and learning achievement of grade VIII-D students in the social sciences subjects. The classroom action research was conducted in three cycles, in which each cycle consists of four phases, namely planning, action, observation, and reflection. The data of the students’ activity were collected from the observation, and the data of the learning achievement were collected from the achievement test. The data were analyzed by using descriptive qualitative analysis. The result of this research showed an improvement in the students’ activity and learning achievement in social sciences subject, shown by the positive progress of the result in each cycle. In the preliminary reflection, the average of students; learning activity was 25,33 the mean score was 70,03 and the learning mastery was 59,38%. At the end of the first cycle, the average students’ learning activity was 65,05 the mean score was 75,49 and the learning mastery was 57,81%. At the end of the second cycle, the average of the students’ learning activity was 80,78 the mean score was 84,48 and the learning mastery was 87.50%. At the end of the third cycle, the average of the students’ learning activity was 89,43 the mean score was 87,50 and the learning mastery was 96,88%. Keyword:            cooperative learning type Group Investigation, learning activity, learning achievement.